EFFECT OF TEMPERATURE ON TEA RED SPIDER MITE (OLIGONYCHUS COFFEAE NIETNER) AND ITS MANAGEMENT USING CYFLUMETOFEN 20 SC - GAUTAM CHAKRABOTRY; D. ROY; P. K. SARKAR (The Bioscan, 2015)
Developmental stages of Tea Red Spider mite (TRSM), Oligonychus coffeae, Nietner (Acari: Tetranychidae) was studied at the laboratory of Department of Agricultural Entomology, BCKV. It was seen that in descending order, the, pre-ovipositional (2.20±0.04 to 1.12±0.03), ovipositional (16.06±0.05 to 10.83±0.18) and post evaporation (76.52±0.14 to 52.30±0.11) period decreased with the increase in temperature. The field trial was conducted at the Sukna Tea Estate,Terai, Darjeeling to evaluate the most effective dose of cyflumetofen 20 SC which at 125 g a.i./ha gave excellent (95 to 100%) reduction and the molecule was found to be soft on natural enemies and all the doses did not produce any phytotoxic symptoms on tea bushes. Further, on contact, it provides good knockdown and long residual activity with excellent plant safety. Maximum average yield of made tea was 621.00 kg m.t./ha in the plots treated with cyflumetofen 20 SC @ 125 g a.i./ha.